IMPACT OF CASHEW GRAFTED PLANTS ADOPTION ON PRODUCTIVITY AND HOUSEHOLD WELFARE IN BENIN - Hinnou Cossi Léonard; Bonou-Zin Dossi Clarisse Régina; Ayedoun O A Alfred (Socio-Economics/Agribusiness Department, 2023)
In Benin, cashew nuts represent a socio-economic and strategic interest for farmers and the government. New technologies, such as grafted plants, have been introduced to improve this crop's productivity. This study used the Propensity Score Matching (PSM) method to assess the impact of adopting cashew grafted plants on land productivity and farm household welfare in Benin. Data were collected from 200 cashew farmers, including 57 adopters and 143 non-adopters of grafted plants. The results revealed that the improvement in cashew nut yield due to adopting grafted cashew plants varies between 231 and 242 kg/ha respectively for Nearest Neighbor and Kernel matching algorithm. Nevertheless, this adoption requires important investments that contribute to increasing agricultural expenses. The results also revealed that grafted plants positively and significantly cashew income and total household income. Grafted cashew plants adopters have an additional 73 755 CFA per hectare cashew income. Total household income also improved by 110 000 CFA per hectare. However, the increase in income needs to be sufficiently large to reduce the proportion of poor among adopters significantly. These results prove that increasing cashew nut production in Benin and improving farmers' welfare will require developing cashew nut planting materials capable of boosting cashew nut productivity. To this end, implementing and diffusing grafted cashew plants throughout the territory requires significant investments to improve cashew productivity and farmers welfare.